ANALYSIS OF THE AVAILABLE SYSTEMS OF SUPPORTING THE SCIENTIFIC ACTIVITIES OF EMPLOYEES OF HIGHER EDUCATIONAL INSTITUTIONS - BOLOTINA, Viktoriia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article provides an analysis of the existing systems of support for the scientific activity of employees of higher educational institutions. In today’s world, in the conditions of the distancing of education, science and other industry of human activity caused by the pandemic and war, there is a need for high-quality and multifunctional software. For scientists at all stages of their activity, it is necessary to use modern web technologies and software. Nowadays, during the full-scale war between Russia and Ukraine, higher education institutions are actively practicing the implementation of web technologies for organizing not only online learning of students and pupils, but also implementing distance work of employees of the higher education institutions, a large part of which is scientific work. In the article we analyze the Open Conference System and the Easy Chair for organization and holding scientific conferences. There are a large number of systems that can perform tasks related to the organization of conference stages, materials management and other important tasks. During the research, it was determined that conference support systems are divided into several types depending on the functionality provided to the user. When people choose a web system for organizing scientific activities of employees, the main criteria is the availability of the resource, which includes convenient functionality, easy start in work, protection of personal materials and personal data. We have determined that among the analyzed systems there is a lack of functionality that would allow us to conduct statistics of employees. Systems for conducting conferences should be expanded in the field of supporting the results of scientific activity.